2021
DOI: 10.1186/s12942-021-00296-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in depressive symptoms by rurality in Japan: a cross-sectional multilevel study using different aggregation units of municipalities and neighborhoods (JAGES)

Abstract: Background Rurality can reflect many aspects of the community, including community characteristics that may be associated with mental health. In this study, we focused on geographical units to address multiple layers of a rural environment. By evaluating rurality at both the municipality and neighborhood (i.e., a smaller unit within a municipality) levels in Japan, we aimed to elucidate the relationship between depression and rurality. To explore the mechanisms linking rurality and depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…1 ). We selected these factors because a rural setting could be related to a higher incidence of depression ( Kanamori et al, 2021 ) and the limited Internet use among older adults ( Kondo et al, 2021 ) and a state of emergency declaration could change the communication modes of older adults ( Arpino et al, 2021 ; Freedman et al, 2021 ; Greenwood-Hickman et al, 2021 ) and make them depressed due to restricted in-person contact ( Briggs et al, 2021 ; Noguchi et al, 2021 ; Sepúlveda-Loyola et al, 2020 ; Zaninotto et al, 2022 ). We calculated the population density of each municipality using the Statistical Observations of Municipalities in 2019 from the Ministry of Internal Affairs and Communications.…”
Section: Methodsmentioning
confidence: 99%
“…1 ). We selected these factors because a rural setting could be related to a higher incidence of depression ( Kanamori et al, 2021 ) and the limited Internet use among older adults ( Kondo et al, 2021 ) and a state of emergency declaration could change the communication modes of older adults ( Arpino et al, 2021 ; Freedman et al, 2021 ; Greenwood-Hickman et al, 2021 ) and make them depressed due to restricted in-person contact ( Briggs et al, 2021 ; Noguchi et al, 2021 ; Sepúlveda-Loyola et al, 2020 ; Zaninotto et al, 2022 ). We calculated the population density of each municipality using the Statistical Observations of Municipalities in 2019 from the Ministry of Internal Affairs and Communications.…”
Section: Methodsmentioning
confidence: 99%
“…Without exception, mental health in rural areas with a high percentage of farmers and fishermen who are relatively more exposed to environmental changes should be the focus of future research in Japan. A recent study found that in Japan, depression was 1.2 times more prevalent in both men and women living in rural compared with urban municipalities 7) . Although the results of that study do not directly indicate that depression is related to ecological grief, they suggest that risk factors for mental distress include the loss of Japan's rural landscape because of fewer farmers as well as declining crop yields and difficulties in maintaining the livestock industry due to global environmental changes.…”
Section: To the Editormentioning
confidence: 97%
“… 15 On the other hand, in rural areas, factors such as the lack of material resources and lower socioeconomic status of residents are commonly suggested as contributing factors to depression. 16 So, finding the association between residence and depression and its interaction by socioeconomic status may provide valuable information for the development of targeted interventions and policies aimed at promoting mental health equity across diverse settings. By addressing the disparities in depression prevalence, we hope to contribute to the overall improvement of mental health in both urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%